2012
DOI: 10.3748/wjg.v18.i47.7100
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor successfully treated with chemotherapy and nonsteroidals: A case report

Abstract: Inflammatory myofibroblastic tumor (IMT) occurring at retroperitoneal sites has rarely been reported. We report the case of a previously well 14-year-old girl with no history of abdominal disease whose past medical history and family tumor history were unremarkable. She complained of intermittent abdominal pain for one month. An abdominal mass was found on physical examination and abdominal contrast-enhanced computed tomography (CT) showed a hypodense soft mass, the size and location of which suggested a well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 0 publications
0
48
0
6
Order By: Relevance
“…Another report describes a mesenteric IMT in a young adult who presented with abdominal pain, weight loss and paraumbilical palpable mass who was treated with complete surgical resection 14. An additional report describes an adult man with a mesenteric IMT who presented with abdominal pain and weakness and was treated with complete surgical resection without recurrence 4. All reports agree that the primary treatment for IMT is complete surgical resection and highlight the importance of close, long-term follow-up to detect local recurrence 4 13 14…”
Section: Discussionmentioning
confidence: 99%
“…Another report describes a mesenteric IMT in a young adult who presented with abdominal pain, weight loss and paraumbilical palpable mass who was treated with complete surgical resection 14. An additional report describes an adult man with a mesenteric IMT who presented with abdominal pain and weakness and was treated with complete surgical resection without recurrence 4. All reports agree that the primary treatment for IMT is complete surgical resection and highlight the importance of close, long-term follow-up to detect local recurrence 4 13 14…”
Section: Discussionmentioning
confidence: 99%
“…Y. Tao и соавт. [45] при не-резектабельной забрюшинной ВМО успешно применили комби-нацию полихимиотерапиии (ПХТ) (метотрексат/цисплатин) в средних дозах с пероральным приемом нестероидных противо-воспалительных препаратов (НПВП). Период безрецидивного незавершенного наблюдения составил более 3 лет.…”
Section: лечение вмо пищеварительного трактаunclassified
“…Tao et al (9) reported an unresectable retroperitoneal IMT, which was successfully treated with methotrexate, cisplatin and diclofenac sodium, facilitating maintenance of a clinical 'free of disease' status for 3 years. Przkora et al (4) also reported a case of unreseactable IMT, treated with anti-inflammatory agent, ibuprofen, where the patient was 'stabilized' for 12 months.…”
Section: Recurrent Retroperitoneal Inflammatory Myofibroblastic Tumormentioning
confidence: 99%
“…The role of radiotherapy in IMT is unknown, although it may have potential benefits, particularly in unresectable cases. To date, there is no established protocol for the treatment of IMT, due to its rarity (9,15).…”
Section: Recurrent Retroperitoneal Inflammatory Myofibroblastic Tumormentioning
confidence: 99%
See 1 more Smart Citation